The Influence of Financial Planning and Investment Decision-Making on Investment Portfolio Performance with the Mediation of Financial Market Knowledge - Sunarmin, Ade Suryana,; Sandra, Jana ? (Program Pascasarjana STIE Amkop Makassar, 2023)
This research explores the complex relationships among financial planning, investment decision-making, financial market knowledge, and investment portfolio performance at Bank DKI - Kantor Kas KS. Tubun. The study uncovers a significant direct link between comprehensive financial planning and improved investment portfolio performance, highlighting the critical role of strategic financial planning in achieving positive outcomes. Additionally, the research identifies a noteworthy indirect effect, suggesting that the favorable impact of financial planning on portfolio performance is partially mediated by the level of financial market knowledge. However, the study finds that the influence of investment decision-making on portfolio performance is not significantly mediated by financial market knowledge. These nuanced findings provide valuable insights into the intricate dynamics of financial strategies within the specific context of the branch, offering meaningful considerations for professionals and researchers in banking, finance, and investment management. Keywords: Soft Skills Training, Managerial Support, Employee Career Development, Self-Confidence